PENGARUH STORE ATMOSPHERE, PROMOTION, PERCEIVED VALUE TERHADAP REVISIT INTENTION DI KEDAI BAKSO PUTRA MANTEP - Ikhwanul Yaqin; Iswati Iswati; Suyono Suyono; Emilia Pranata (CV. Denasya Smart Publisher, 2025)
This study aims to determine “the influence of store atmosphere, promotion, and perceived value on revisit intention at Kedai Bakso Putra Mantep.” This study uses a quantitative method with data collection techniques through questionnaires distributed to customers of Kedai Bakso Putra Mantep with a total of 98 respondents. Data analysis was conducted using multiple linear regression to test the relationship between independent variables (store atmosphere, promotion, perceived value) and the dependent variable (revisit intention). The results of the study indicate that store atmosphere and perceived value have a significant influence on revisit intention, while promotion has a lower influence compared to the other two variables. The implication of this study is that Putra Mantep Meatball Shop needs to improve the aspects of comfort and perceived value for customers to increase the likelihood of repeat visits.